PRIMARY ANGIOSARCOMAS OF THE BONE: AN EVALUATION OF 4 CASES - Yılmaz, Selçuk; Atalay, İsmail Burak; Öztürk, Recep (Journal of Ayub Medical College Abbottabad, 2021)
Angiosarcoma is a rare mesenchymal neoplasm that may arise from vascular or lymphatic tissue. Angiosarcoma of bone is a rare high-grade malignant vascular tumour, representing less than 1% of all angiosarcomas. The most common locations of unifocal tumour are the long and short tubular bones, followed by the pelvis, and trunk. The literature regarding treatment and outcome of patients with this tumour is limited. We performed a retrospective study to analyse treatment and survival of four patients with angiosarcoma of bone. Keywords: Angiosarcoma of bone; Angiosarcoma; Bone tumour